Adjusting the accuracy of PEGDA-GelMA vascular network by dark pigments via digital light processing printing. (February 2022) - Sheng, Lin; Li, Mo; Zheng, Shuxian; Qi, Jian
Vascularization is one of the most important factors greatly influencing scaffold regeneration. In this study, a precise network of hollow vessels was printed by digital light processing (DLP) with poly(ethylene glycol) diacrylate (PEGDA)/gelatin-methacryloyl (GelMA), and dark pigmentation absorbers were added to ensure printing accuracy. First, the compound bio-inks of the PEGDA-GelMA hydrogel were prepared for direct vascular printing, and a high-precision DLP system was established. Second, the printing effects of three dark absorbers, namely, nigrosin, brilliant black, and brilliant blue, on the x -, y -, and z -axes were studied. By printing models with different densities, it was determined that 0.2% nigrosin, 0.1% brilliant black, and 0.3% brilliant blue had better effects on the x - and y -axes accuracy, and the absorbance of the absorbers played a decisive role in adjusting the accuracy. Additionally, to solve the problem of uneven curing on the upper and lower surfaces caused by the addition of an absorber with high absorbance, a model of the difference in curing width between the upper and lower surfaces of a unit-layer slice based on high-absorbance absorbers was established, and the reference value for the slice thickness was calculated. Third, the biological and mechanical properties of the bio-inks were verified with scanning electron microscopy and Fourier transform infrared, and by tensile, swelling, degradation, and cytotoxicity tests on different concentrations of PEGDA-GelMA hydrogel and absorbers. The results showed that 30% PEGDA-7% GelMA/0.1% brilliant black was the optimal preparation to print a hollow vascular network. The error of the printing tube wall and cavity was between 1% and 3%, which demonstrates the high precision of the method. Human umbilical vein endothelial cells were planted in the lumen, and the survival rate achieved 107% on the seventh day, demonstrating the good biocompatibility of the composite hydrogel.